Coasting along to a wider range: niche conservatism in the recent range expansion of the Tawny Coster, Acraea terpsicore (Lepidoptera: Nymphalidae). Issue 3 (23rd November 2020) - Chowdhury, Shawan; Braby, Michael F.; Fuller, Richard A.; Zalucki, Myron P.
Abstract: Aim: The Tawny Coster Acraea terpsicore is a highly mobile butterfly that has recently expanded its spatial distribution from South Asia to South‐East Asia and Australia. Here, we determine if the realized climatic niche has changed during the expansion and analyse the geographic pattern of spread in Australia. Location: Asia and Australia. Methods: We collated occurrence records, divided the geographic range into three spatio‐temporal phases (pre‐expansion, early‐expansion and late‐expansion) and then developed ecological niche models for each phase. To determine whether the realized niche has changed during the range expansion, we performed a principal component analyses and niche overlap analysis. Finally, we calculated the annual rate of range expansion to estimate the speed and pattern of geographic spread. Results: The climatic niche of A. terpsicore differs only slightly in the pre‐expansion and late‐expansion ranges and was most distinct in the early‐expansion range. The species' range in Australia expanded at an average rate of ~ 135 km/year (range: 34–359 km/year). Female‐biased migration occurred in north‐eastern Queensland at the leading edge of the range, the first documentation of this phenomenon in butterflies. Main Conclusions: Acraea terpsicore represents one of the fastest documented geographic range expansions of any species, highlighting how rapidly butterflies can colonize new areas, even where environmental conditions are substantially different to those in their original distribution. However, we found little evidence of climatic niche shift, and only a minor niche shift is apparent in the early‐expansion and late‐expansion ranges. It remains unclear what triggered the sudden expansion, but it has been hypothesized that tropical deforestation provided conditions that initiated local range expansion, and further work on the possible mechanisms involved is required.